Comparing the treatment needs of participants with co-occurring mental health and substance use disorders in drug and veterans treatment courts. (3rd May 2020) - Clary, Kelsey M.; Shaffer, Paige M.; Gaba, Ayorkor; Pinals, Debra A.; Smelson, David
ABSTRACT: Objective: Despite the growing research on the effectiveness of specialty courts, including drug treatment courts (DTCs) and veterans treatment courts (VTCs), little is known about the unique treatment needs of individuals with co-occurring mental health and substance use disorders (COD) who are commonly served by these courts. This pilot study examines individuals with COD across two DTCs and two VTCs in Massachusetts to understand the characteristics and treatment needs of these unique populations. Methods: Baseline data for 112 individuals enrolled in a community-based COD treatment program within two DTCs ( N = 86) and two VTCs ( N = 26) with a Monte Carlo simulation of 10, 000 samples were analyzed to assess differences in treatment needs. Results: DTC participants experienced more lifetime convictions ( p = .000), months incarcerated ( p = .000), and had a longer lifetime history of illicit drug use ( p = .004). Meanwhile, a higher proportion of VTC participants experienced trauma ( p < .002) and chronic medical problems ( p < .001), and VTC participants experienced more severe acute behavioral health symptoms as measured by the BASIS-32 ( p = .021). Conclusions: Given the unique differences in treatment needs between DTC and VTC participants, these findings have implications for specialty court management such as treatment planning, referrals to meet participants' service needs, and even docket sizes.